Changes in the physico-chemical attributes through processing of salami made from blesbok (Damaliscus pygargus phillipsi), eland (Taurotragus oryx), fallow deer (Dama dama), springbok (Antidorcas marsupialis) and black wildebeest (Connochaetes gnou) in comparison to pork. (December 2018) - Chakanya, Chido; Arnaud, Elodie; Muchenje, Voster; Hoffman, Louwrens C.
Abstract: Drying kinetics and changes in proximate composition, pH, salt content, water activity (aw ) and lipid oxidation through processing of salami made using five different game meat species were evaluated and compared to pork. Eight batches of salami from each species were made and sampled for analysis throughout processing. Processing time was a significant factor on all measured attributes whilst species affected ( P  ≤ .05) pH and moisture but not drying kinetics. Black wildebeest meat exhibited higher ( P  ≤ .05) pH than pork and other game meat (6.30 vs 5.63–5.80), which translated to higher ( P  ≤ .05) salami pH throughout and at the end of processing (5.77). Final pH of all other salami ranged from 5.01 to 5.28, aw ranged from 0.88 to 0.92. TBARS remained lower than 1 mg MDA equivalent/kg. The study suggests that salami from these game species, excluding black wildebeest, can be produced using the same processing parameters as conventional pork salami and obtaining similar physico-chemical attributes. Highlights: Salami produced from different game meat species was compared to a conventional pork based salami. Results show minimal species differences; similar drying kinetics and physico-chemical attributes to a pork based salami. Higher initial pH of black wildebeest meat effected differences in some physico-chemical attributes of the salami.